Perbuatan Melawan Hukum dalam Kasus Penyerobotan Tanah : Studi Putusan No.202/Pdt.G/2023/Pn Lbp - Emima Yohana Nasution; Selfenia Nofelita Sitinjak; Iwan Setyawan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Land encroachment is one of the most prevalent forms of land disputes in Indonesia, causing significant harm to lawful landowners. This study examines the Decision of the Lubuk Pakam District Court Number 202/Pdt.G/2023/PN Lbp, which adjudicated a case between three holders of Land Ownership Certificates (Sertifikat Hak Milik/SHM) against PT Perkebunan Nusantara II (PTPN II) Sei Semayang Estate. On March 15, 2020, the defendant unilaterally entered the plaintiffs' land using heavy machinery to destroy crops and demolish buildings, subsequently seizing physical control of the land and planting sugarcane over it. This study aims to: (1) analyze the application of the elements of Unlawful Acts (Perbuatan Melawan Hukum/PMH) under Article 1365 of the Civil Code within the aforementioned decision; (2) assess the consistency of the decision with PMH theory and prior judicial precedents in similar cases; and (3) describe the juridical implications of the decision for all parties involved. The research employs a normative juridical method using a case study approach with descriptive-analytical characteristics. The findings reveal that the Panel of Judges of the Lubuk Pakam District Court applied all four elements of PMH cumulatively and comprehensively. First, the element of unlawful conduct was established because the act of eigenrichting (self-help) was carried out without a final and binding court judgment invalidating the plaintiffs' ownership certificates. Second, the element of fault was established as the defendant's actions were premeditated and intentional, evidenced by a coordination meeting held prior to the takeover and the deployment of security personnel during its execution. Third, the element of damages was established through the destruction of crops and buildings valued at over IDR 7.9 billion, as well as non-material losses. Fourth, the element of causal nexus was directly and irrefutably established. The decision also demonstrates strong consistency with PMH theory derived from the LindenbaumCohen Arrest of 1919 and relevant Supreme Court jurisprudence. The juridical implications of the decision for the defendant include a legally binding declaration of PMH, an obligation to return the land, and the imposition of a coercive fine (dwangsom) of IDR 100,000 per day of non-compliance. For the plaintiffs, the decision reaffirms the validity of their land certificates and provides a legal foundation for restoring physical possession of the land. At a macro level, this decision reinforces the principle of legal certainty in Indonesia's land administration system and affirms that no party, including state-owned enterprises, may unilaterally seize property rights without undergoing the proper legal procedures.